Goldenhar syndrome with new oral findings! - Vela D Desai (Wolters Kluwer Medknow Publications, 2021)
Goldenhar syndrome (GS) is a condition with a multitude of abnormalities, classically involving ocular and ear defects, hemifacial microsomia, and vertebral anomalies, which may also be associated with cardiovascular and renal malformations. It is a rare congenital anomaly of unclear etiology. The purpose of reporting this case of a 16-year-old boy with GS is, to update, the existing literature of new oral findings observed.